ANALYSIS OF THE IMPLEMENTATION OF INDEPENDENT LEARNING-INDEPENDENT CAMPUS (MBKM) IN IMPROVING STUDENT COMPETENCE BASED ON INDUSTRIAL NEEDS - Kadarisman Hidayat; Abd. Qadir Muslim; Langgeng Setyono (Halu Oleo University, 2023)
As a breakthrough from the Indonesian Ministry of Education and Culture, Research and Technology, the Merdeka Learning Kampus Merdeka (MBKM) program needs to measure the effectiveness of its implementation in increasing student competence based on industrial needs from the perspective of the three parties involved, namely students as learners, teaching staff/study programs, and partners/industry. This research was conducted at the University of Brawijaya. The research method uses a quantitative approach with a survey research type. The population of this study was students who were accepted into the MBKM program in the 2021/2022 academic year; as many as 694 students were active in the MSIB, IISMA, Semeru, Student Exchange, and Bangkit UB programs, while the population of Lecturers/ Study Programs totals 76 study programs, as well as partners/industry where 100 students take part in MSIB activities so that the total population is 870 respondents. Therefore, the sample for this study was obtained from 269 respondents using the Krejcie & Morgan formula. They are collecting data in this study using a questionnaire. The collected data were processed using SPSS and Microsoft Excel tools to display descriptive data about the perspectives of the three parties. The research results show that implementing the Independent Campus Learning Policy (MBKM) in Improving Student Competence Based on Industrial Needs at Brawijaya University is very good; this is evident from the results of a survey conducted on lecturers, students, and MBKM partners.